Identification of Atherosclerosis Based on The Differences in Cholesterol and Creatinine in Indonesia with Multivariate Analysis of Variance - Maulana Achiar, Anshari Luthfi; Aidi, Muhammad Nur; Kurnia, Anang; Widoretno, Widoretno (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Atherosclerosis is a chronic inflammatory disease indicated by plaque build-up in the arteries due to increased total cholesterol, low-density lipoproteins (LDL), triglycerides, and decreased high-density lipoproteins (HDL). It is also associated with disruption of renal function high creatinine blood level. This study aims to identify atherosclerosis based on differences in total cholesterol, HDL, LDL, triglycerides, and creatinine levels in 35.509 residents from 33 provinces and rural-urban areas in Indonesia. This study uses two-factor MANOVA where the province and rural-urban are the factors, followed by ANOVA and Tukey's test. Results show differences between total cholesterol, HDL, LDL, triglyceride, and creatinine levels of the residents among provinces and rural-urban areas. The Residents from Bangka Belitung and North Sulawesi provinces have the highest risk of atherosclerosis, and Jambi province has the most balanced condition. Urban residents tend to be at risk for atherosclerosis due to high levels of LDL, while rural residents are at risk by low HDL or high creatinine levels